1999
DOI: 10.1016/s0022-2275(20)32142-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of remnant-like particles isolated by immunoaffinity gel from the plasma of type III and type IV hyperlipoproteinemic patients

Abstract: Previous studies have investigated the potential atherogenicity and thrombogenicity of triglyceride-rich lipoprotein (TRL) remnants by isolating them from plasma within a remnant-like particle (RLP) fraction, using an immunoaffinity gel containing specific anti-apoB-100 and anti-apoA-I antibodies. In order to characterize lipoproteins in this RLP fraction and to determine to what extent their composition varies from one individual to another, we have used automated gel filtration chromatography to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…It should be noted that little of the apoA-I component of the unbound fraction (ϳ2 mg/dl) would likely be present in total plasma RLP, as a Mab to apoA-I is included, together with Mab JI-H, in the RLP reagent (2). Marcoux et al found only 0.3% of plasma apoA-I in plasma RLP from normolipidemic subjects (5).…”
Section: Properties Of Lipoproteins Distinguished By Affinity For Mab Ji-hmentioning
confidence: 98%
See 4 more Smart Citations
“…It should be noted that little of the apoA-I component of the unbound fraction (ϳ2 mg/dl) would likely be present in total plasma RLP, as a Mab to apoA-I is included, together with Mab JI-H, in the RLP reagent (2). Marcoux et al found only 0.3% of plasma apoA-I in plasma RLP from normolipidemic subjects (5).…”
Section: Properties Of Lipoproteins Distinguished By Affinity For Mab Ji-hmentioning
confidence: 98%
“…Since that time, a considerable body of literature has supported the utility of RLP-C concentration as a risk marker for atherosclerotic disease (3). It has been recognized, however, that the test for RLP-C in particular includes not only the described fraction of TRL, but also certain lipoproteins of higher density (2,(4)(5)(6).…”
mentioning
confidence: 99%
See 3 more Smart Citations